Hledani souvislosti mezi kvalitou zivotniho prostredi a vybranymi demografickymi charakteristikami - Andel, J (Demografie, 1989)
The relationship between changes in demographic variables and the deterioration of the environment is explored. The data concern the North Bohemian region of Czechoslovakia, the area with the most damaged environment, as well as the Czech part of Czechoslovakia. The results show that environmental deterioration has a negative effect on total mortality, infant mortality, health-related migration, and abortion. (SUMMARY IN ENG AND RUS)
Keywords: Developed Countries; Demography; Europe, Eastern; vyspělé země; mortalita; východní Evropa; populace; Population Dynamics; Evropa; služby plánování rodičovství; životní prostředí; Environmental Pollution; Environment; emigrace a imigrace; Environmental Degradation; kojenecká mortalita; Migration; Population; znečištění životního prostředí; Europe; Mortality; Eastern Europe; populační dynamika; Československo; Abortion, Induced; Demographic Factors; Czechoslovakia; Infant Mortality; Family Planning; Family Planning Services; demografie; Fertility Control, Postconception; indukovaný potrat; Emigration and Immigration